The Optimal Regulation of Credit Rating Agencies - Josef Forster (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
Credit rating agencies (CRAs) very often have been criticized for announcing inaccurate credit ratings and are suspected of being exposed to conflicts of interest. Despite these objections CRAs remained largely unregulated. Based on Pagano & Immordino (2007), we study the optimal regulation of CRAs in a model where rating quality is unobservable and enforcing regulation is costly. The model shows that minimum rating standards increase the social value of credit ratings. The model also analyzes implications for regulation in the presence of conflicts of interest between the CRA and the rated clients by direct bribes and by the joint provision of rating and consulting services.
urn:nbn:de:bvb:19-epub-5169-8
Keywords: G20; G24; G28; 330; credit rating agencies; regulation; conflicts of interest; Ratingagentur; Dienstleistungsqualität; Regulierung; Lieferantenmanagement; Patronage; Theorie